External quality assurance of chest X-ray interpretation to strengthen diagnosis of childhood TB - B.F. Melingui; E. Leroy-Terquem; J.V. Taguebue; T.C. Eap; L. Borand; C. Khosa; R. Moh; J. Mwanga-Amumpaire; S. Beneteau; M.T. Eang; I. Manhiça; A. Mustapha; et al. (IJTLD Open)
BACKGROUND: Chest X-ray (CXR) misinterpretation negatively affects the accuracy of childhood TB diagnosis. External quality assurance (EQA) could strengthen CXR reading skills. We assessed the uptake, performance and challenges of an EQA of CXR interpretation within the childhood TB-Speed decentralisation study in six resource-limited countries. METHODS: Every quarter, TB suggestive or unreadable CXRs and 10% of remaining CXRs from children with presumptive TB were selected for blind re-reading by national re-readers. The proportion of CXRs selected for EQA and re-read assessed the uptake. The performance was assessed by the proportion of discordant interpretations and the sensitivity and specificity of clinicians’ vs re-readers’ interpretations. Challenges were retrieved from country reports. RESULTS: Of 513 eligible CXRs, 309 (60.8%) were selected for EQA and 278/309 (90.0%) re-read. The proportion of discordant interpretation was between 13/48 (27%) in Sierra Leone and 7/13 (53.8%) in Cote d’Ivoire during the first EQA and decreased after the EQAs periods in 3/5 countries. Clinician sensitivity reached 100% in all countries over EQA. Specificity ranged between 13% in Sierra Leone and 65% in Cambodia (first EQA) and increased in 4/5 countries after the EQA periods. CXR transfer and re-readers’ workload were the main challenges. CONCLUSION: EQA can enhance CXR interpretation for childhood TB diagnosis, provided operational challenges are overcome.